VD_FINDINFO Jug / 2011 / 234 vom 25. August 2011 - VD Tribunal cantonal (2011)
RESPONSABILITÉ DES ORGANES D'UNE SOCIÉTÉ, SOCIÉTÉ ANONYME, DOMMAGE DIRECT, DOMMAGE INDIRECT | 716 CO, 716a CO, 716b CO, 717 CO, 754 CO, 755 CO, 757 CO, 759 CO, 260 LP